Trends in the quality and hygiene parameters of bulk Italian Mediterranean buffalo (Bubalus bubalis) milk: A three year study. (29th September 2017) - Pasquini, Marina; Osimani, Andrea; Tavoletti, Stefano; Moreno, Itzhak; Clementi, Francesca; Trombetta, Maria Federica
Abstract: Buffalo milk represents an indispensable source of nourishment in many parts of the world and it is the second most consumed milk worldwide. Buffalo milk is actually used for the production of many dairy products such as pasteurized or concentrated milk, butter, yogurt, ice‐cream, dehydrated milk products and cheeses. Due to its high nutritional value and the presence of natural bioactive substances, buffalo milk can also provide health benefits to consumers. In Italy, buffalo milk is used mainly for cheese making, mozzarella PDO (Protected Designation of Origin), which is a highly valued dairy product. This 3‐year study, carried out between 2011 and 2013, was aimed at evaluating the quality of bulk Italian Mediterranean buffalo milk by monitoring physico‐chemical parameters, somatic cell and total bacterial counts. A total of 51 samples of bulk milk were collected from one herd throughout the monitored period. Analysis of variance, carried out to test month, season and year main effects, highlighted remarkable seasonal effects for fat, protein and lactose content, as well as for predicted mozzarella cheese yield, and somatic cell counts. The calculation of simple correlations allowed the identification of positive correlations between estimated cheese yield and fat and protein content.